Exacerbation of Autoimmune Bullous Diseases After Severe Acute Respiratory Syndrome Coronavirus 2 Vaccination: Is There Any Association? - Kianfar, Nika; Dasdar, Shayan; Salehi Farid, Ali; Balighi, Kamran; Mahmoudi, Hamidreza; Daneshpazhooh, Maryam (Frontiers in Medicine, 2022)
Background and aim There have been concerns regarding the potential exacerbation of autoimmune bullous diseases (AIBDs) following vaccination against COVID-19 during the pandemic. In the current study, vaccine safety was evaluated in patients with AIBDs. Methods In this study, patients with AIBDs were contacted via face-to-face visits or phone calls. Patient demographics, vaccine-related information, pre- and post-vaccine disease status, and complications were recorded. The exacerbation was considered either relapse in the remission/controlled phase of the disease or disease worsening in the active phase. The univariate and multivariate logistic regression tests were employed to determine the potential risk factors of disease exacerbation. Results Of the patients contacted, 446 (74.3%) reported receiving at least one dose of vaccine injection (54.7% female). Post-vaccine exacerbation occurred in 66 (14.8%) patients. Besides, there were 5 (1.1%) patients with AIBD diagnosis after vaccination. According to the analysis, for every three patients who received vaccines during the active phase of the disease one experienced disease exacerbation. The rate of disease exacerbation increased by three percent with every passing month from the last rituximab infusion. Active disease in the past year was another risk factor with a number needed to harm of ten. Moreover, the rate of disease exacerbation increased by 3 percent with every passing month from the last rituximab infusion. Conclusions Risk of AIBD exacerbation after the COVID-19 vaccine is not high enough to prevent vaccination. This unwanted side effect, can be reduced if the disease is controlled at the time of vaccination.